Spatial Constellation Design for MIMO Visible Light Communication Based on the Optimal Geometric Shaping - Jia-Ning Guo; Jian Zhang (IEEE Photonics Journal)
As a wireless communication which combines illumination and communication, visible light communication (VLC) has attracted great attention. In indoor VLC systems, multiple illumination devices are commonly employed, forming a natural multi-input multi-output (MIMO) communication system. In this paper, a spatial constellation design based on the optimal geometric shaping is proposed for the MIMO-VLC system with the peak-power and total average-power constraints. Firstly, we derive the optimal geometric shaping region for the MIMO-VLC system under the aforementioned power constraints. Subsequently, we intersect the scaled integer lattice with the optimal geometric shaping region and combine it with minimum-energy mapping to obtain a spatial constellation. Simulation results for indoor MIMO-VLC systems verify the superiority of our approach compared to conventional methods.